2010
DOI: 10.1155/2010/395785
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Delta Reduces Oxidative Stress in Primary Human Renal Tubular Cells

Abstract: Erythropoietin (EPO) exerts (renal) tissue protective effects. Since it is unclear whether this is a direct effect of EPO on the kidney or not, we investigated whether EPO is able to protect human renal tubular epithelial cells (hTECs) from oxidative stress and if so which pathways are involved. EPO (epoetin delta) could protect hTECs against oxidative stress by a dose-dependent inhibition of reactive oxygen species formation. This protective effect is possibly related to the membranous expression of the EPO r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 44 publications
2
13
1
3
Order By: Relevance
“…Due to its NO dioxygenase activity (56 -58), CYGB might reduce intracellular NO concentration, which in turn may prevent accumulation of peroxynitrite, a strong oxidant formed from the reaction between superoxide and NO. It has been speculated that CYGB, like other hexacoordinated globins, may eliminate reactive oxygen species utilizing heme and thiol residues (59,60), and it has been found that CYGB may reduce the induction of intracellular reactive oxygen species formation (55,61). The processes of lipid-induced transformation of CYGB from hexacoordinate to pentacoordinate may allow the cell to up-regulate antioxidant defenses before extensive oxidative damage occurs (62).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its NO dioxygenase activity (56 -58), CYGB might reduce intracellular NO concentration, which in turn may prevent accumulation of peroxynitrite, a strong oxidant formed from the reaction between superoxide and NO. It has been speculated that CYGB, like other hexacoordinated globins, may eliminate reactive oxygen species utilizing heme and thiol residues (59,60), and it has been found that CYGB may reduce the induction of intracellular reactive oxygen species formation (55,61). The processes of lipid-induced transformation of CYGB from hexacoordinate to pentacoordinate may allow the cell to up-regulate antioxidant defenses before extensive oxidative damage occurs (62).…”
Section: Discussionmentioning
confidence: 99%
“…The protective antioxidant capability of epoetin   δ   was then assessed using a commercial oxidative status indicator (2′, 7′-dichlorodihydrofluorescein diacetate; H 2 DCFDA). The authors have demonstrated that epoetin   δ   antioxidant capacity has protected the renal tissue through upregulation of several renoprotective genes, some of them, as carboxypeptidase M, dipeptide peptidase IV, and cytoglobin, were reported for the first time to be involved in the antioxidant renoprotection process [105]. …”
Section: Antioxidant Therapeuticsmentioning
confidence: 99%
“…Recent studies have demonstrated that NFAT and AP1 induce Cygb expression, thus mediating calcineurin signalling [55]. Moreover, Cygb expression has been found as a downstream target of tumour growth factor b (TGF-b), platelet-derived growth factor, protein kinase C [26] and EPO signalling [56]. The Cygb signalling pathway is illustrated in Fig.…”
Section: Gene Regulationmentioning
confidence: 99%